2018
DOI: 10.12891/ceog4113.2018
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle thickness in women with polycystic ovary syndrome

Abstract: Objective: To evaluate pelvic floor muscle (PFM) thickness in women with polycystic ovary syndrome (PCOS) group and compare it to those with normal menstrual cycle (control group). Materials and Methods: Transperineal ultrasound examination was used to evaluate the thickness of the bilateral pelvic floor muscles Results: The mean age was 25.1 ± 2.1 and 24.2 ± 1.9 years in PCOS and control groups, respectively (p > 0.05). Body mass index averaged 22.5 ± 0.9 in the control group and 27.8 ± 2.6 in the PCOS group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A different claim was reported by Antonio et al, who have shown no difference in the PFMs strength between PCOS women and those of the control group [13]. Another study found no difference in the frequency of reporting urine loss between PCOS and control groups with normal BMI and BMI > 25 [18]. On the contrary, this study showed that the women in the PCOS group had higher scores in the urinary distress inventory-6 domain of the PFDI-20 compared to the non-PCOS group (control) of a matched BMI.…”
Section: Discussionmentioning
confidence: 77%
“…A different claim was reported by Antonio et al, who have shown no difference in the PFMs strength between PCOS women and those of the control group [13]. Another study found no difference in the frequency of reporting urine loss between PCOS and control groups with normal BMI and BMI > 25 [18]. On the contrary, this study showed that the women in the PCOS group had higher scores in the urinary distress inventory-6 domain of the PFDI-20 compared to the non-PCOS group (control) of a matched BMI.…”
Section: Discussionmentioning
confidence: 77%